A view to a kill. Renaissance paintings as living objects - de Klerck, Bram (Incontri. Rivista europea di studi italiani, 2019)
Review of Elsje van Kessel, The Lives of Paintings. Presence, Agency and Likeness in Venetian Art of the Sixteenth Century (Studien aus dem Warburg Haus, vol. 18), Berlin, De Gruyter, Leiden, Leiden University Press, 2017.